El estampillado de billetes de banco. Alteración de un documento económico como medio de propaganda - De Francisco Olmos, José María (Revista General de Información y Documentación, 2004)
This article reviews the events experienced by a specific economic document, in this case Banco de España banknotes, as a consequence first of the political changes which occurred in the state of issue ( change of political regime from monarchy to republic in Spain) and then of the outbreak of civil war which divided the country into two parallel states which fought not only on the field of battle but on all fronts, including the economic which led to the economic and monetary breakup of Spain. The article shows how in these years the banknote, issued by a private entity, the Banco de España, is `counterstamped’ by the political power for its own private ends, changing its outward appearance and jeopardizing its acceptance in both internal and foreign circulation, all this mainly through legal texts emanating from the political authority.